Do they feel like they don't matter? The rural-urban divide in external political efficacy - García del Horno, Rubén; Rico, Guillem; Hernández, Enrique (West European politics, 2024)
Rural areas have often been labelled by the literature as 'left-behind' areas or 'places that don't matter', implicitly suggesting that residents of these communities feel neglected by political elites. This article studies the rural-urban divide in external political efficacy, which reflects individuals' beliefs about the responsiveness of political elites, while also examining if compositional and contextual factors can explain such a divide. Drawing on data from the European Social Survey, the results reveal a significant rural-urban gap in external efficacy, which is partly explained by differences in the sociodemographic characteristics of rural and urban dwellers, but not by disparities in their evaluation of the provision of basic public services. Notably, this rural-urban gap in external efficacy is substantively smaller in those countries with higher levels of electoral malapportionment that lead to an overrepresentation of rural areas in national parliaments.